Cultural pressures and the Conflict of Gender roles For working women in leadership positions A field study of a sample of Female leaders - Ghiat, Hayat; Fatima Zohra, Meriah (International Journal of Psychosocial Rehabilitation, 2022)
The present study aims to reveal the socio-cultural pressures experienced by working women in leadership positions. In addition to this, the paper also aims to investigate the conflict of roles experienced by women in leadership. The study sample is composed of 200 working women in leadership positions, in a range of different fields, including: (directors of educational institutions at all levels, heads of hospital departments, departments, managers of industrial and commercial institutions, heads of social services departments, and inspectors in customs). Based on previous research, a study scale that examines the pressures and conflicting responsibilities of female leaders was constructed, serving as a questionnaire to test the hypotheses. The tool was used on the primary study sample after its validity and dependability were confirmed. The percentages were determined using the descriptive statistics method once the researcher had extracted the results. It also used the SPSS statistical package’s inferential statistics method to calculate the correlational and other associations between the variables.